Two Theories of American Literature: Insights Into Faulkner's Southern Garden - Rita Terezinha Schmidt (Ilha do Desterro)
This paper has a two-fold purpose. First, to draw a parallel between two theoretical approaches to American Literature as presented in Henry Nash Smith's Virgin Land (1950) and Leo Marx' The Machine in the Garden (1964) in order to examine how these studies, reciprocally interlocked by their concern with the master image of the American landscape, provide valuable conceptual tools for the understanding of the interdependence of literature, environment, socio-economic context and the collective imagination. Second, to investigate the extent to which some of these tools can be organized into a coherent framework which, applied to Faulkner's "The Bear" (Go Down, Moses, and Other Stories, 1942) illuminates the basic issues which sustain and determine its meaning.